Produção de ácido hialurônico microbiano: viabilidade econômica e avaliação de impactos ambientais - Harth, Matheus Lopes (Universidade Federal de São Carlos, 2022)
Hyaluronic acid is a biopolymer with unique structural and rheological properties, that, initially, was produced by extraction from animal tissue, from rooster comb. However, it used non-ecofriendly solvents (chloroform) and high purification costs to remove contaminants from the rooster comb motivated its manufacture from Streptococcus zooepidemicus bacteria cultivation. Considering this, our study proposed to do a techno-economic-environmental analysis of microbial hyaluronic acid production incorporated to a bioethanol biorefinery with S. zooepidemicus. The techno-economic analysis was conducted in EMSO, while the environmental analysis was done via Life Cycle Analysis, with the approach of gate-to-gate. At first, sugarcane juice was evaluated as carbon source and the required steam and electricity were provided from the sugarcane factory, which resulted in a net present value (NPV) of US$ 18.43 million with a return-on-investment rate of 12.5%. Economic feasibility can enhance further by utilizing more fractions from the biorefinery, such as yeast surplus for yeast extract production and not adding the salts to the cultivation medium, which increase NPV in 37.1% and 11.6%, respectively. From the environmental point-of-view, the Life Cycle Analysis showed the step with more environmental impact was the Production, especially the sodium hydroxide consumption for the cleaning-in-place and pH control, representing 78% of the total impact for Global Warming Potential. As the cleaning-in-place cannot be suppressed due to rules of regulatory agencies, we assessed the effect of not controlling the cultivation pH and assess its impact by reducing sucrose conversion to 50%. Such change made the process economically unfeasible, confirming what the shaken flasks cultivation showed: pH control has a significant effect on the cultivation of S. zooepidemicus, especially in the growth aspect of it.
Microbial hyaluronic acid production: economic feasibility and environmental impacts assessment
Keywords: Ácido hialurônico; Hyaluronic acid; Avaliação técnico-econômica; Techno-economic analysis; Análise de ciclo de vida; Life cycle assessment; Avaliação técnico-econômica-ambiental; Techno-economic-environmental analysis; Streptococcus zooepidemicus; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA